Heavy metals in horseshoe crab egg (Tachypleus gigas) - Wan Nawang, Wan Nur Fatin Syafiqah (2012)
Heavy metals concentrations were evaluated for horseshoe eggs and sediments from two different sites (Sitiawan, Perak and Banting, Selangor). Eggs and sediments samples were digested then heavy metals determined using Inductively Couple Plasma-Mass Spectrometer. Nine elements detected in eggs and sediments were Arsenic (As), Cadmium (Cd), Copper (Cu), Ferum (Fe), Magnesium (Mg), Nickel (Ni), Lead (Pb), Selenium (Se), and Zinc (Zn). The concentration of these elements (ppm) in eggs from Sitiawan ranged from 0 - 0.833 ppm for As, 0.0307 – 0.0553 ppm for Cd, 0.268 – 0.457 ppm for Cu, 0.213 – 0.733 ppm for Fe, 1.773 – 7.443 ppm for Mg, 0.014 – 0.020 ppm for Ni, 0.012 – 0.029 for Pb, 0.016 – 0.024 ppm for Se and 0.309 – 0.565 for Zn. As for Banting, As ranged from 0 – 0.026 ppm, Cd: 0.012 -0.067 ppm, Cu: 0.032 – 1.282 ppm, Fe: 0.567 – 2.153 ppm, Mg: 5.820 – 30.133 ppm, Ni: 0.036 – 0.048 ppm, Pb: 0.047 – 0.024 ppm, Se: 0.037 – 0.019 ppm, and Zn: 0.416 – 0.437 ppm. There were significant differences (p<0.05) in As, Cd and Cu concentrations before and after 28 days incubation for horseshoe crab eggs from Banting. Only As and Cd differed significantly for eggs from Sitiawan. These results showed that As, Cd and Cu were definitely increased in horseshoe crabs eggs after incubation. However, eggs samples used for each respectively sites were of pooled eggs. It is possible that some of the eggs clumps were of different maternal sources, therefore may have caused the high variations in the metals concentrations. Sediments samples analysis showed that sediments from Sitiawan are highly contaminated with As, Cd, Cu, Fe, Mg, Ni and Pb when compared to Banting. However, Zn was higher Banting, while Se only detected in Banting sediments. This study also showed that autoclaving process does not affect all elements in the sediments except for Mg.